Analisis Strategi Keunggulan Bersaing (Competitive Advantage) Sektor Usaha Kecil Menengah di Kota Gorontalo (Studi Industri Meubel di Kota Gorontalo) - Idris Yanto Niode (BISMA (Bisnis dan Manajemen), 2018)
This research aims to: (1) Identified and analyzed the factors that would influences external and internal environment of SMEs in order to maintain their competitive advantages; (2) to found and analyzed what kind of effort that SMEs and government does in order to maintain and supporting the competitive advantage of SMEs at Gorontalo; (3) to analyzed the competitive advantage strategy of SMEs to winning the competition. The method used in this research is a survey method by doing data collection from interviewing, observation, and questionnaire spread up. Analysis doing by identified current external and internal environment, until move to the particular circumstances of competitive advantage strategy in the future. In order to formulating the competitive advantage strategy, researcher used SWOT analysis. The result shown, to achieve competitive advantage between competitors, SMEs must use œaggressiveœ Strategy which is by decreasing a cost, create new product, quality improvement, market expansion. In addition another strategy based on SWOT matrix that could used to achieve competitive advantage are: create a fresh business plan; get more credit to have more capital; fixing and improving product quality; labor insurance (work safety); enter and conquer the market; service quality improvement; and promotion intensity.